Nordic Media Histories of Propaganda and Persuasion - Norén, Fredrik; Stjernholm, Emil; Thomson, C. Claire (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XIV, 331 p. 22 illus.